2011
DOI: 10.1177/0022034511402209
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Periodontitis Prevalence among Chronic Kidney Disease Patients

Abstract: Because of adverse effects of uremia in the innate and adaptive immune systems, we hypothesized that chronic kidney disease (CKD) patients would have higher prevalence of moderate periodontitis compared with individuals without CKD. We examined this hypothesis using the NHANES III dataset, including 12,081 adults stratified by Race-Ethnicity. We followed the American Academy of Periodontology/Centers for Disease Control and Prevention definition for moderate periodontitis. Estimated glomerular filtration rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 27 publications
3
66
0
Order By: Relevance
“…A recent cohort study showed that severe periodontitis is associated with kidney dysfunction in African Americans (Grubbs et al, 2015). Other clinical studies have also demonstrated a close association between CKD and periodontal disease (Ioannidou & Swede, 2011; Iwasaki et al, 2012). …”
Section: Introductionmentioning
confidence: 84%
“…A recent cohort study showed that severe periodontitis is associated with kidney dysfunction in African Americans (Grubbs et al, 2015). Other clinical studies have also demonstrated a close association between CKD and periodontal disease (Ioannidou & Swede, 2011; Iwasaki et al, 2012). …”
Section: Introductionmentioning
confidence: 84%
“…First, compared with previous studies (Kshirsagar et al, 2005;Fisher et al, 2008), we used a more recent periodontitis case definition (Page and Eke, 2007), which has been adopted in official US public health publications on the national prevalence of periodontitis (Dye et al, 2007). This is important, since we have shown previously that the choice of periodontitis case definition affects associations with renal function (Ioannidou and Swede, 2011). Second, we estimated GFR based on cystatin C levels, which have been shown to provide more accurate estimates compared with creatinine, which depends heavily on muscle mass, age, sex, and race (Stevens et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…History of cardiovascular disease (CVD) was constructed as a variable derived from the self-reported history of heart attack, stroke, heart failure, and hypertension (Kshirsagar et al, 2008). Education and income variables were constructed as reported previously (Ioannidou and Swede, 2011), whereas Body Mass Index (BMI) was calculated as body weight (kgr) divided by squared height (m 2 ) and was stratified into 4 standard categories.…”
Section: Materials and Methods Study Populationmentioning
confidence: 99%
“…Chronic periodontitis constitutes one of the factors that contribute to the development of chronic kidney disease, and the relationship between those two entities is bi-directional [15][16][17][18][19].…”
Section: Chronic Kidney Disease and Periodontal Statusmentioning
confidence: 99%